Insufficient Sleep Syndrome in Childhood - Teruhisa Miike (Children)
Sleep disorders in children have a negative impact on mental and physical development, and a lack of sleep is one of the most important problems in infancy. At the age when naps are commonly accepted, the judgment of whether the amount of sleep is adequate has been based on the total amount of sleep per day. In other words, the idea is that even if the amount of sleep at night is insuﬃcient, it is not considered insuﬃcient if it is compensated for by taking a long nap or sleeping late on weekend mornings. However, these lifestyle habits disrupt the circadian rhythm and cause social jet lag, which is not appropriate for healthy mental and physical development. Therefore, in this review, I present the average required nighCime basic sleep duration (NBSD) of 10 h for Japanese and 11 h for Caucasian children as a judgment standard. (1) If the child sleeps less than 8 h at night, and (2) if the child sleeps less than 9 h at night or 30 to 60 min less than the required NBSD, immediate treatment is recommended. I also discuss briefly how to address sleep insufficiency in childhood.